System or process? A meta-theoretical reflection on the nature of the firm - Vladislav Valentinov (Systemic Practice and Action Research, 2022)
The paper revisits the fundamental question of the nature of the firm by contrasting two philosophic worldviews suggested by process philosophy and the Luhmannian systems theory. Whereas the former worldview takes reality to be internally related, the latter ones underscores the tendency of social systems, such as firms, to disregard much of this interrelatedness.~The productive tension between these worldviews suggests that the firm provides a context where systemic imperatives meet the rich concrete reality of human life. The role of the firm is to house those aspects of this reality that are too organic to be accommodated by the abstract "language of prices" corresponding, in institutional economics terms, to the reliance on market governance. The major examples of these aspects explored in the paper are dynamic capabilities and business ethics, both of which hold the potential to improve the firm's sustainability, both economic and social. The proposed contrast between the process-philosophic and systems-theoretic worldviews thus illuminates not only the nature of the firm but also the managerial relevance of corporate sustainability instruments.
Keywords: 330; business ethics; process philosophy; systems theory; theory of the firm